277 Combined neoadjuvant chemo-immunotherapy therapy achieves superior downstaging of resectable non-small cell lung cancer as compared to chemotherapy, mono or dual immunotherapy. (9th November 2020) - Sepesi, Boris; Corsini, Erin; Weissferdt, Annikka; Pataer, Apar; Altan, Mehmet; Antonoff, Mara; Blumenschein, George; Elamin, Yasir; Fossella, Frank; Glisson, Bonnie; Hofstetter, Wayne; Kurie, Jonathan; et al.
Abstract : Background: Tumor and nodal downstaging following neoadjuvant therapy in resectable non-small cell lung cancer (NSCLC) are important markers of therapeutic response associated with favorable prognosis. We studied the impact of four different systemic neoadjuvant therapies on tumor, nodal and overall pathological downstaging of surgically resectable I-IIIA NSCLC (AJCC 7th edition). Methods: Our study cohorts consisted of NSCLC patients treated with three cycles of neoadjuvant platinum doublet chemotherapy from 2001–2012 (N=302, 84%), and patients treated on the NEOSTAR study (NCT03158129 ) who received neoadjuvant nivolumab (N=21, 6%), nivolumab plus ipilimumab (N=16, 4%), or platinum doublet chemotherapy plus nivolumab (N=22, 6%). Clinical and pathological (yp) T and N staging were evaluated for downstaging and upstaging; differences were assessed using Fisher's exact test. Results: Following neoadjuvant platinum doublet chemotherapy, nivolumab, nivolumab plus ipilimumab and platinum doublet chemotherapy plus nivolumab, the rates of clinical-to-pathological ypT downstaging were 26% (N=79), 29% (N=6), 38% (N=6) and 59% (N=13), respectively, p =0.012 (table 1 ). The rates of clinical-to-pathological ypN downstaging in patients with clinical N1 or N2 disease with each therapy were 55% (N=96), 50% (N=3), 50% (N=2), and 42% (N=5) respectively, p =0.862. Overall clinical-to-pathological (ypT and/or ypN) downstaging rates were 38% (N=114), 38% (N=8), 38% (N=6), and 68% (N=15) respectively, p=0.048. The proportions of patients being overall upstaged following each therapy were 28% (N=85), 38% (N=8), 38% (N=6) and 14% (N=3), respectively, p=0.251. These results suggest superior downstaging effect and clinically meaningful lower upstaging probability of combined platinum doublet chemotherapy plus nivolumab as compared to other neoadjuvant regimens. Conclusions: The combination of neoadjuvant platinum doublet chemotherapy with nivolumab achieves the most robust tumor and overall pathological downstaging and decreases the probability of upstaging at surgery. Whether the overall downstaging effect results in improved survival will be determined with longer follow-up, in conjunction with results from ongoing phase III neoadjuvant chemo-immunotherapy trials. Trial Registration: NCT03158129 Ethics Approval: This study was approved by the University of Texas MD Anderson Institutional Review Board with a waiver of informed consent, protocol 2020-0337.